Synthesis and characterization of silver nanoparticles using Ocimum gratissimum root extract and their biological activities against some clinical pathogens - Chioma Mercy Nzerema; Prince Joe Nna; Kingsley John Orie (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2025)
This study investigates the green synthesis of silver nanoparticles (AgNPs) using Ocimum gratissimum root extract, along with their characterization and antibacterial efficacy. Proximal analysis revealed low moisture (8.02 ± 0.11%), crude protein (3.31 ± 0.28%), crude fat (2.01 ± 0.59%), moderate fibre (9.18 ± 0.40%), and ash (5.11 ± 0.91%), indicating a carbohydrate-rich composition. AgNPs were synthesized using the root extract as reducing and stabilizing agent; UV–Vis spectroscopy confirmed their formation with a surface plasmon resonance peak at 425 nm, consistent with spherical nanoparticles (30–100 nm). FTIR identified phenolic and polysaccharide functional groups (O–H, C=O, C–O), while XRD indicated a face-centered cubic (FCC) structure with good crystallinity. SEM micrographs showed mostly spherical particles with minimal aggregation. Antimicrobial activity at 10–20 mg/mL was tested against Proteus mirabilis, Pseudomonas aeruginosa, Bacillus cereus, Aspergillus fumigatus, Candida albicans, and Saccharomyces cerevisiae. The root extract alone showed no activity at 10 mg/mL but exhibited dose-dependent inhibition at higher concentrations (ZOIs: 10.40–15.16 mm). AgNPs displayed stronger broad-spectrum efficacy (ZOIs: 7.12–18.9 mm), often surpassing gentamicin. These findings highlight the potential of O. gratissimum root-derived AgNPs as eco-friendly antibacterial agents against multidrug-resistant organisms.